Ant Colony Optimization Technique Based Harmonic Suppression in Active Power Filters - M. Madhusudhan Reddy; P.Srinivasa Varma; D. Lenine (International Journal of Integrated Engineering, 2024)
This work recommends an innovative scheme for atonement of the reactive powers and minimization of harmonics with the application of Ant Colony based Optimization algorithm (ACOA) to achieve a preferred proportional and integral controller gain, which is applied to the shunt connected active filters. The utilization of dynamic eager heuristic, positive feedback &distributed evaluation are the key preferences for the ACOA algorithm. An ACOA constructed improved PI controller is recommended to supersede the common PI controller which contributes in exceptional trail of DC power in APF under nonlinear load (NLL) circumstances. Moreover, there is a demand to confirm the strength of the ACOA algorithm, the outcomes are presented and equated to the particle swam optimization (PSO) based PI controller. The active filters are utilized in this analysis to minimize the global harmonic distortion of the source current in addition to the further parameters like active & reactive powers are observed and correlated by applying nature influenced algorithms like ACOA and PSO to attain the superior results. The suggested investigation can be carried out in the Matlab/Simulink software.